Pengaruh Tinggi Muka Air Tanah Gambut terhadap Evolusi Gas CO2 - Sigit Aji Wiyatno; Abdul Hadi; Zuraida Titin Mariana (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2024)
This study aims to determine the effect of the groundwater level on the evolution of CO2 in peat soils if the groundwater table is lowered from a depth of 40 cm (PP No. 57 of 2016 concerning protection and management of peat ecosystems) to a depth of 60 cm. This study was conducted in a greenhouse and Laboratory of Physics, Chemistry and Biology Department of Soil, Agriculture Faculty, ULM. This study was began in October 2021 and continued until February 2022. The research method used was a factorial Completely Randomized Design (CRD) with four replications. The factors tested were the water table of the peat at a depth of 0 cm just above the soil surface (T1), 20 cm below the soil surface (T2), 40 cm below the soil surface (T3), and 60 cm below the soil surface (T4). The results of this study showed that the CO2 evolution of peat soil during incubation for 1, 2, 3, 7, 14, 21, and 28 days at a depth of 20 cm was not significantly different from a depth of 40 cm and 60 cm, but significantly different when the groundwater level was right at the surface soil. The CO2 evolution of peat soils at groundwater levels at the soil surface was lower than water levels 20, 40, and 60 cm below the ground.